Minimal basilar membrane motion in low-frequency hearing - Warren, Rebecca L.; Ramamoorthy, Sripriya; Ciganovic, Nikola; Zhang, Yuan; Wilson, Teresa M.; Petrie, Tracy; Wang, Ruikang K.; Jacques, Steven L.; Reichenbach, Tobias; Nuttall, Alfred L.; Fridberger, Anders (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Low-frequency hearing is critically important for speech and music perception, but no mechanical measurements have previously been available from inner ears with intact low-frequency parts. These regions of the cochlea may function in ways different from the extensively studied high-frequency regions, where the sensory outer hair cells produce force that greatly increases the soundevoked vibrations of the basilar membrane. We used laser interferometry in vitro and optical coherence tomography in vivo to study the low-frequency part of the Guinea pig cochlea, and found that sound stimulation caused motion of a minimal portion of the basilar membrane. Outside the region of peak movement, an exponential decline in motion amplitude occurred across the basilar membrane. The moving region had different dependence on stimulus frequency than the vibrations measured near the mechanosensitive stereocilia. This behavior differs substantially from the behavior found in the extensively studied high-frequency regions of the cochlea.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Basilar membrane; Hair cells; Hearing; Optical coherence tomography